2020
DOI: 10.1002/mds.27970
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal Deep Brain Stimulation Reduces Sensorimotor Cortex Activation in Focal/Segmental Dystonia

Abstract: Background Although deep brain stimulation of the globus pallidus internus (GPi‐DBS) is an established treatment for many forms of dystonia, including generalized as well as focal forms, its effects on brain (dys‐)function remain to be elucidated, particularly for focal and segmental dystonia. Clinical response to GPi‐DBS typically comes with some delay and lasts up to several days, sometimes even weeks, once stimulation is discontinued. Objective This study investigated how neural activity during rest and mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Deep brain stimulation (DBS) has been used over the last three decades to successfully treat the symptoms of a number of neurological and a few psychological disorders (Benabid et al, 1987;Mayberg et al, 2005). By far the most common disorders treated with DBS are movement disorders such as Parkinson's disease (PD; Deuschl et al, 2006) and essential tremor (ET; Kupsch et al, 2006). PD is a movement disorder, with recognizable symptoms of tremor, slowness of movement and stiffness (Lees et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) has been used over the last three decades to successfully treat the symptoms of a number of neurological and a few psychological disorders (Benabid et al, 1987;Mayberg et al, 2005). By far the most common disorders treated with DBS are movement disorders such as Parkinson's disease (PD; Deuschl et al, 2006) and essential tremor (ET; Kupsch et al, 2006). PD is a movement disorder, with recognizable symptoms of tremor, slowness of movement and stiffness (Lees et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tisch et al showed that using transcranial magnetic stimulation (TMS) paired with associative stimulation (PAS) reduced LTP-like motor cortex plasticity ( 10 ). The study by Andrea Greuel et al demonstrated that GPi-DBS normalized dystonia-associated sensorimotor and prefrontal hyperactivity in patients with focal/segmental dystonia ( 11 ). Therefore, GPi stimulation appears to regulate distant network nodes through the basal ganglia-thalamus-cortical circuit, which may explain the slow onset of the benefits of DBS in managing dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…EEG performed five years after DBS showed slow-wave discharges, with no evidence of generalized spike or polyspikes from prefrontal or frontal that had been seen in the previous EEG. A study investigating the effect of chronic Gpi-DBS on brain activity in focal and segmental dystonia revealed markedly reduced resting cerebral blood flow (rCBF) in the prefrontal cortex in patients who underwent Gpi-DBS for dystonia [ 49 ]. The mechanism of decreased activity in the prefrontal network in dystonia after Gpi DBS may be different from the decrease in glucose metabolism in the prefrontal cortex in PHM.…”
Section: Discussionmentioning
confidence: 99%